4x+12-2x=3x-9

Simple and best practice solution for 4x+12-2x=3x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+12-2x=3x-9 equation:


Simplifying
4x + 12 + -2x = 3x + -9

Reorder the terms:
12 + 4x + -2x = 3x + -9

Combine like terms: 4x + -2x = 2x
12 + 2x = 3x + -9

Reorder the terms:
12 + 2x = -9 + 3x

Solving
12 + 2x = -9 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
12 + 2x + -3x = -9 + 3x + -3x

Combine like terms: 2x + -3x = -1x
12 + -1x = -9 + 3x + -3x

Combine like terms: 3x + -3x = 0
12 + -1x = -9 + 0
12 + -1x = -9

Add '-12' to each side of the equation.
12 + -12 + -1x = -9 + -12

Combine like terms: 12 + -12 = 0
0 + -1x = -9 + -12
-1x = -9 + -12

Combine like terms: -9 + -12 = -21
-1x = -21

Divide each side by '-1'.
x = 21

Simplifying
x = 21

See similar equations:

| (x-2)x=224 | | 7y+4x=42 | | 72=1.5x | | a=1.2(h-84) | | 16h-72b=4h-30 | | 4c+11-7n=-13 | | 1+3x+3=-11 | | h=-4+7t-5t^2 | | 8a=0.48 | | 4xy+6yz-5xz-4xy= | | 33.33x+y=4 | | 5y+12-8y=-42 | | x+(x*.13)=49.15 | | 9-9x=-171 | | 8x=10x-6 | | 8x+7x-4=4x+5x-9 | | 13x-3=x+53 | | 11+7q=12+6q | | 7b+7=6b | | -3+5x-3x=-15 | | -7-2j=5j | | 3k-5-7k=-37 | | 2lnx=21 | | 4x-1=-3x+13 | | 3x+42-5x=2-9x+5 | | X+5x=450 | | X+4+2x=20 | | 3lnx=22 | | 3(5x-2)+3(9-2x)-2(4x+1)=-1 | | 0.505=0.505x | | a(p+q)+2b(p+q)+a(p-q)+2b(p-q)= | | -3(3p+3)-2(4-8p)-3(9+2p)=0 |

Equations solver categories